PENOLAKAN GARUDA INDONESIA TERHADAP PENUMPANG YANG DISEBABKAN KARENA PENEMPATAN HAND BAG DI LANTAI PESAWAT (STUDI KASUS PUTUSAN MAHKAMAH AGUNG NOMOR 2733 K/PDT/2018) - Ricardo Calvin Enoni Nazara; Sugandi Ishak (Fakultas Hukum Universitas Tarumanagara, 2021)
In aviation activities, sometimes disputes occur due to misunderstandings between passengers and cabin crew, and even lead to lawsuits in court. The problem faced is how the attitude of airplane passengers should be according to Law Number 1 of 2009 concerning Aviation and what actions can be taken by the Garuda Indonesia airline against passengers who violate the provisions of air transportation. The results show that the attitude of airplane passengers according to Law Number 1 of 2009 concerning Aviation (Case Study of Supreme Court Decision Number 2733 K/Pdt/2018) refers to Article 54 of Law Number 1 of 2009 concerning Aviation. Passengers are prohibited from violating the rules that have been implemented by the flight service provider, and disrupting the flight, and the captain of the aircraft has the authority to take action such as lowering the passenger. Actions that can be taken by Garuda Indonesia against passengers who violate the provisions of air carriage are that Garuda Indonesia must notify that the rules are so. Garuda Indonesia's obligation is to announce the conditions of carriage, and others. The terms of carriage are in the announcement. The conditions of carriage at Garuda Indonesia are regulated in Article 1 to Article 18 regarding the conditions of carriage regarding passengers and baggage. To prevent disturbance of order and comfort while using air flight services, of course, awareness of all stakeholders is needed in complying with all applicable legal regulations.